Autologous fibroblasts for the treatment of cutaneous loxoscelism: First experience. Issue 6 (17th September 2019) - Guglielmetti, Antonio; Jahr, Catalina; Gompertz‐Mattar, Matías
Abstract: Several treatments have been described for cutaneous loxoscelism (CL), but the quality of available evidence is insufficient for the elaboration of a therapeutic consensus. Dapsone has shown beneficial effects on stopping the inflammatory phenomenon and accelerating the recovery. It is recommended to start dapsone once the visceral involvement is ruled out if glucose‐6‐phosphate dehydrogenase levels are normal. Autologous fibroblast (AF) therapy is a novel therapy that has been successfully used in bioengineering as skin substitutes for surgical wounds and burns, diabetic and pressure ulcers, and other aesthetic purposes. Interestingly, there are no reports of AFs in CL. We present a case of CL in which the necrotic process was stabilised with dapsone, but the healing of the ulcer was not achieved. Three weekly applications of AFs 100 000/cm 2 were performed on a biocompatible polymer matrix, with optimal response within 2 months. This represents the first report of AFs in CL, setting the stage for future studies.